2020
DOI: 10.1002/jcp.29671
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor microenvironment in the regulation of PD‐L1: A novel role in resistance to cancer immunotherapy

Abstract: Tumor evasion from the host immune system is a substantial strategy for tumor development and survival. The expression of many immune checkpoint proteins in cancer cells is a mechanism by which tumor cells escape from the immune system.Among the well-known immune checkpoints that can tremendously affect tumor development and cancer therapy are the programmed death-ligand-1/programmed death-1 (PD-L1/PD-1). To tackle this phenomenon and improve the therapeutic strategies in cancer treatment, the blockade of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 174 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Tumor cells bind to PD-1 on tumor-infiltrating lymphocytes via PD-L1. This interaction induces lymphocyte apoptosis, allowing tumor cells to resist destruction and achieve immune escape [ 70 , 71 ]. The PD-L1/PD-1 signaling axis mediates immune escape in the tumor microenvironment [ 68 ]; PD-L1 is selectively expressed on the surface of cancer cells, and its binding to PD-1 on the surface of activated T cells results in negative regulatory signal transmission, which decreases immune activity [ 72 , 73 ].…”
Section: Tumor Immune Escapementioning
confidence: 99%
“…Tumor cells bind to PD-1 on tumor-infiltrating lymphocytes via PD-L1. This interaction induces lymphocyte apoptosis, allowing tumor cells to resist destruction and achieve immune escape [ 70 , 71 ]. The PD-L1/PD-1 signaling axis mediates immune escape in the tumor microenvironment [ 68 ]; PD-L1 is selectively expressed on the surface of cancer cells, and its binding to PD-1 on the surface of activated T cells results in negative regulatory signal transmission, which decreases immune activity [ 72 , 73 ].…”
Section: Tumor Immune Escapementioning
confidence: 99%
“…The immunosuppressive TME is known to help the cancer cells evade the immune system (126). For example, apoptotic tumor cells are rarely recognized as antigens, and TME has the ability to upregulate the expression of regulatory T (Treg) cells or myeloidderived suppressor cells and downregulate that of the cytotoxic T cells (127).…”
Section: Use Of Exosome In Combination With Cancer Immunotherapymentioning
confidence: 99%
“…Microvesicles originate directly from the budding of plasma cellular membranes and range in size from 200 to 1000 nm. The smallest EVs derived from endosomes with 30–150 nm diameter are called exosomes, in which different microenvironmental conditions can affect different amounts of exosome production and also various components at the cargo level. , Extensive studies have reported the critical role of exosomes in immune regulation, differentiation, apoptosis, angiogenesis through passing immunomodulatory cytokines, and noncoding RNAs (ncRNAs) like miRNAs between immune cells and other cell populations. Notably, several ncRNAs can be transferred by exosomes including microRNA (miRNAs), long noncoding RNA (lncRNAs), and circular RNA (circRNAs), which are the most attractive because of their role in intercellular communication …”
Section: Introductionmentioning
confidence: 99%